2016
DOI: 10.1021/jacs.6b03472
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Porous Conjugated Polymers and Roles of Residual Palladium for Photocatalytic Hydrogen Production

Abstract: Developing highly efficient photocatalyts for water splitting is one of the grand challenges in solar energy conversion. Here, we report the rational design and synthesis of porous conjugated polymer (PCP) that photocatalytically generates hydrogen from water splitting. The design mimics natural photosynthetics systems with conjugated polymer component to harvest photons and the transition metal part to facilitate catalytic activities. A series of PCPs have been synthesized with different light harvesting chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
334
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(350 citation statements)
references
References 37 publications
15
334
1
Order By: Relevance
“…Residual palladium has been suggested to act as cocatalysts in photocatalytic hydrogen evolution in covalent triazine-based frameworks, [37] and in conjunction with g-C 3 N 4 . [38] Low thresholds for the effect of residual palladium on the photocatalytic performance has been reported in conjugated microporous polymers, [22] and for Au loaded onto La-doped NaTaO 3 . [39] It is unclear whether the amount of residual palladium, difference in molecular weight, crystallinity, hydrophobicity or a combination of all of these factors affect the photocatalytic performance in comparison to P8-i.…”
Section: Doi: 101002/aenm201700479mentioning
confidence: 99%
See 1 more Smart Citation
“…Residual palladium has been suggested to act as cocatalysts in photocatalytic hydrogen evolution in covalent triazine-based frameworks, [37] and in conjunction with g-C 3 N 4 . [38] Low thresholds for the effect of residual palladium on the photocatalytic performance has been reported in conjugated microporous polymers, [22] and for Au loaded onto La-doped NaTaO 3 . [39] It is unclear whether the amount of residual palladium, difference in molecular weight, crystallinity, hydrophobicity or a combination of all of these factors affect the photocatalytic performance in comparison to P8-i.…”
Section: Doi: 101002/aenm201700479mentioning
confidence: 99%
“…[18,19] We have shown that a series of conjugated microporous polymers (CMPs) could facilitate hydrogen evolution from water in the presence of a sacrificial electron donor, without any additional heavy metal cocatalyst. [20,21] Other CMPs have since been studied for photocatalysis [22,23] and recent studies have demonstrated that linear conjugated polymers can have high photocatalytic activities. [24,25] However, as with g-C 3 N 4 , none of these organic materials are soluble in common organic solvents.…”
mentioning
confidence: 99%
“…Subsequently, Li et al introduced donor-acceptor type microporous polymer by co-polymerization method [44]. Two types of monomeric units, electron-rich units (M2-M4) and electron-deficient (M1) units, were copolymerized with different ration of weak donor biphenyl and weak acceptor bipyridine to produce a series of four polymers (Figure 7).…”
Section: Conjugated Microporous Polymers (Cmps)mentioning
confidence: 99%
“…Of course, such varying composition of the catalysts makes it difficult to carry out stable and reproducible synthetic procedures [18]. Nanoparticle contamination and the effect of residual metal have been discussed for a variety of catalytic transformations and metal salts used [19][20][21][22][23]. Indeed, structural variations induced by trace metal impurities lead to several difficulties and to irreproducible optoelectronic function [24].…”
Section: Catalyst Decomposition and Vendor-dependent Purity Of Metal mentioning
confidence: 99%
“…For example, ICP-MS measurements have shown an increase of the residual Pd content in the range of 0.04-1.88 % upon changing the catalyst/monomer ratio [23]. Several other analytic tools, such as inductively coupled plasmaoptical emission spectroscopy (ICP-OES), ion chromatography (IC), atomic absorption (AA) and X-ray fluorescence (XRF), can also be used.…”
Section: Catalyst Decomposition and Vendor-dependent Purity Of Metal mentioning
confidence: 99%